The diagnostic role of endoscopic ultrasonography, magnetic resonance imaging and computed tomography in the assessment of pancreatic cystic lesions - Beyza Olcay Öztürk; Nergiz Ekmen; Mehmet Cindoruk; Güner Kılıç; Ali Karataş; Hadi Sasani; Murat Uçar (National Scientific Medical Center, 2021)
Aim: To reveal the malignancy rates of pancreatic cyctic lesions and success rates of computed tomography (CT), magnetic resonance imaging (MRI) and endoscopic ultrasonography (EUS) in differentiating between malignant vs non-malignant cystic lesions of the pancreas. Methods: In this study, 138 patients  were included. CT, MRI, EUS and pathology reports of the related patients were scrutinised and descriptive statistical methods were used. Sensitivity and specificity values of  CT, MRI and EUS were calculated by taking the postoperative histopathology results as the gold standard. Results: In assessment the data of patients with neoplastic or non-neoplastic pancreatic cysts,  the highest sensitivity, specificity and diagnostic accuracy in the malignant-benign distinction of the lesions was determined in CT.   Although EUS had similar sensitivity and diagnostic accuracy rates as CT, its specificity was considered to be lower than CT.  MRI had lower sensitivity, specificity and diagnostic accuracy rates compared to both of modalities (EUS and CT). The sensitivity, specificity and diagnostic accuracy of EUS guided FNA biopsies were found to be quite low than other diagnostic modalities. Conclusion: While CT and EUS showed high correlation with each other in terms of overall diagnostic compliance, there was a moderate correlation between MRI and EUS.